Wally and Mae - Kempter, Christa; Weldin, Frauke (New York : NorthSouth, 2010)
A very neat rabbit and a messy, fun-loving bear learn about toleration and compromise.
K-3
Accelerated Reader AR
Keywords: Toleration -- Fiction; Friendship -- Fiction